Logistics Technology Innovation and Operational Efficiency : Assesing Cost of Goods Sold (COGS) in Reduction in Medium-Sized Manufacturing Firms. - Rustandi, Bambang (CV. HEI PUBLISHING INDONESIA, 2026)
This study aims to analyze the effect of logistics technology (logtech) management innovations on the reduction of Cost of Goods Sold (COGS) in medium-sized manufacturing firms. The study employs a quantitative approach using a survey method involving 30 respondents selected through purposive sampling. Data were analyzed using the Partial Least Squares – Structural Equation Modeling (PLS-SEM) method with the assistance of SmartPLS. The results indicate that logtech has a significant negative effect on COGS, with a coefficient of -0.73, a t-statistic of 6.21, and a p-value < 0.05. The coefficient of determination (R²) of 0.61 indicates that the logtech variable explains 61% of the variation in COGS reduction. These findings suggest that increased adoption of logistics technologies, such as Warehouse Management Systems (WMS), Transportation Management Systems (TMS), and the Internet of Things (IoT), contributes to improved supply chain efficiency and reduced production costs. This study offers a theoretical contribution to the development of operations management literature as well as practical implications for companies in designing logistics digitization strategies to enhance cost efficiency and competitiveness.